The absence of aldehyde dehydrogenase 1 A1-positive cells in benign mammary stroma is associated with risk factors for breast cancer - Isfoss BL (Dove Medical Press, 2016)
Björn Logi Isfoss,1–3 Bo Holmqvist,1,4 Helena Jernström,1 Per Alm,1 Håkan Olsson1,5 1Department of Oncology and Pathology, Department of Clinical Sciences Lund, Lund University, 2Department of Pathology, Skane University Hospital, Lund, Sweden; 3Department of Pathology, Telemark Hospital, Skien, Norway; 4ImaGene-iT AB, Medicon Village, 5Division of Cancer Epidemiology, Department of Clinical Sciences, Lund University, Lund, Sweden Abstract: In this study, aldehyde dehydrogenase 1 (ALDH1)-expressing cells in stroma of histologically normal breast tissue from premenopausal women were investigated in situ regarding cellular morphology, cell distribution, and relation to the additional stem cell markers, CD44 (+) and CD24 (–). These results were correlated with hormonal and genetic risk factors for breast cancer. Triple immunofluorescence labeling was performed on tissues from premenopausal women with a family history of breast cancer, and breast reduction specimens from premenopausal women with no family history of breast cancer were used as a control group. The majority of ALDH1-immunoreactive cells in stroma were spindle-shaped or polygonal, and such cells that were CD44– and CD24– were absent in the breast stroma of a significantly larger number of nulliparous than parous women. A less common morphological type of ALDH1-positive cells in stroma was round or oval in shape, and such cells that were CD44+ and CD24– were absent in a significant number of women with a family history of breast cancer. The CD44+/CD24– immunophenotype is consistent with stem cells, and the round/oval morphology suggests mesenchymal cells. This study demonstrates that there are two morphologically distinct types of ALDH1-positive cells in histologically benign mammary stroma, and the absence of these cells is correlated with clinical risk factors for breast cancer in premenopausal women. Keywords: mammary glands, human, neoplasms, BRCA1 gene, stem cells, immunohistochemistry